Efisiensi Penerimaan Dana Zakat Baznas Provinsi Jawa Barat dengan Metode Data Envelopment Analysis (DEA) - Nur Azizah; Encep Abdul Rojak; Akhmad Yusuf (Bandung Conference Series: Sharia Economic Law, 2022)
Absstract. In 2016 the receipt of zakat funds at BAZNAS Prov. West Java experienced a decrease of 15.63% and in 2020 by 40.58%. Meanwhile, the increase in zakat fund receipts occurred in 2018 by 51.59% and in 2019 by 7.32%. Based on the potential receipt of zakat funds in West Java Province in 2017 it reached Rp. 217 Trillion. The zakat receipt data shows that the receipt of zakat funds from BAZNAS West Java Province has not approached the potential figure that has been calculated based on the National Zakat Index. This shows the need to evaluate the performance of BAZNAS in West Java Province. Based on this explanation, further research needs to be done to determine the level of efficiency and what factors are behind the efficiency or not of receiving zakat in BAZNAS West Java Province for the 2016-2020 period. In this study using quantitative methods and primary data sources in the form of official documents and secondary data in the form of supporting data and data collection techniques, namely the documentation technique. The data that has been collected is then processed using the Data Envelopment Analysis (DEA) method with a Variable Return to Scale approach. (VRS) and Constant Return to Scale (CRS). The results of this study indicate that the performance of the BAZNAS of West Java Province with the VRS method experienced efficiency in 2016, 2018 and 2020, but there was inefficiency in 2017 and 2019, while the CRS method experienced efficiency in 2016, 2018, 2019, and 2020, but inefficiency occurred in 2017. Abstrak. Pada tahun 2016 penerimaan dana zakat di BAZNAS Provinsi Jawa Barat mengalami penuruan sebesar 15.63% dan pada tahun 2020 sebesar 40.58%. Sedangkan kenaikan penerimaan dana zakat terjadi pada tahun 2018 sebesar 51.59% dan pada tahun 2019 sebesar 7.32%. Berdasarkan potensi penerimaan dana zakat di Provinsi Jawa Barat yang mencapai angka Rp. 17,6 Triliun, data peneriman zakat tersebut menunjukan bahwa penerimaan dana zakat BAZNAS Provinsi Jawa Barat belum mendekati angka potensi yang telah dihitung berdasarkan Indeks Zakat Nasional. Hal ini menunjukkan perlunya evaluasi terhadap kinerja BAZNAS Provinsi Jawa Barat. Berdasarkan pemaparan tersebut perlu dilakukan penelitian lebih lanjut untuk mengetahui tingkat efisiensi dan faktor apa saja yang melatarbelakangi efisien atau tidaknya penerimaan zakat di BAZNAS Provinsi Jawa Barat periode 2016-2020. Dalam penelitian ini menggunakan metode kuantitatif dan sumber data primer berupa dokumen resmi dengan data sekunder yaitu berupa data pendukung dan teknik pengumpulan data menggunakan teknik dokumentasi. Data yang sudah terkumpul kemudian diolah dengan menggunakan metode Data Envelopment Analysis (DEA) dengan pendekatan Variable Return to Scale (VRS) dan Constant Return to Scale (CRS). Hasil penelitian ini menunjukkan bahwa kinerja BAZNAS Provinsi Jawa Barat dengan metode VRS mengalami efisiensi pada tahun 2016, 2018 dan 2020, tetapi terjadi inefisiensi pada tahun 2017 dan 2019, sedangkan dengan metode CRS mengalami efisiensi pada tahun 2016, 2018, 2019, dan 2020, tetapi terjadi inefisiensi pada tahun 2017.